IMPLEMENTASI KEBIJAKAN PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA TERHADAP PEREMPUAN DI KELURAHAN KUNINGAN, KECAMATAN SEMARANG UTARA, KOTA SEMARANG - Intani Mardalina, Dian; Puspo Priyadi, Budi; Hayu Dwimawanti, Ida (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This research began with the high number of cases of violence against women in Kuningan Village. The type of violence most often experienced by women is Domestic Violence (KDRT). On the other hand, Kuningan Village has the Women and Children Protection Network (JPPA) as the right arm of DP3A which operates in the field of women and children at the village level. JPPA Kuningan Village has guidelines in carrying out its duties, one of which is PERDA Number 5 of 2016. In PERDA Number 5 of 2016 Article 15 paragraph 2 explains seven efforts to prevent violence against women. Therefore, it is interesting to analyze more deeply the implementation of policies by JPPA in efforts to prevent acts of violence against women in the household in Kuningan Village. This research uses qualitative descriptive methods by collecting data through interviews and documentation. The results showed that the JPPA Kuningan Village has not fully implemented this policy. They are judging from the analysis of inhibiting factors using Van Metter and Van Horn's theory with six influencing components. Inhibiting factors that influence include resources, characteristics of implementing agents, economic, social and political conditions, as well as disposition of implementers. As for the aspects of standars and objectives and communication between organizations and strengthening activities they are good.